Molecular Control of Human Embryonic Development: A Comprehensive Study - Shifan, Khanday (Journal of Embryology, 2025)
Human embryonic development is a highly coordinated and complex process that transforms a single fertilized cell into a fully formed human organism. This process is governed by intricate molecular mechanisms involving genetic regulation, signal transduction pathways, and intercellular communication. This study explores key molecular pathways controlling human embryonic development, focusing on the roles of morphogens, transcription factors, signaling molecules, and epigenetic modifications. By reviewing the most recent literature and experimental studies, we aim to highlight the molecular orchestration that directs cell fate decisions, tissue patterning, and organogenesis in humans.
Keywords: Human Embryonic Development; Molecular Control; Morphogens; Transcription Factors; Signal Transduction; Epigenetic Regulation